PENGARUH LEVERAGE, RETURN ON ASSET (ROA) DAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK DENGAN TRANSPARANSI SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arimurti, Trias; Astriani, Devi; Sabaruddin (KRISNA: Kumpulan Riset Akuntansi, 2022)
This study examines and analyzes the effect of leverage, return on assets (ROA), and capital intensity on tax avoidance with transparency as a moderating variable. The data used in this study are secondary data which is sourced from the company's financial statement data on the Indonesia Stock Exchange. The population in this study. These are all manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling with criteria tailored to the needs of the study. From the specified criteria, 37 companies were obtained as samples. The data analysis method used panel data regression with tools: Eviews 10 analysis and Moderating Regression Analysis (MRA). The results show that, first, leverage does not have a positive effect on tax avoidance. This shows that the higher the debt funding from third parties used by the company. The higher the interest costs arising from the debt, so that it will reduce the company's tax burden, not making the company financing with large amounts of debt. Second, ROA has a positive effect on tax avoidance. This shows that the higher the company's profitability, the better the corporate tax planning because it can result in tax optimization, and the company's tendency to do tax avoidance is decreasing. Third, capital intensity. This shows that the depreciation expense originating from the company's fixed assets does not significantly affect the company's tax reduction.